Legionella effector Ceg10 acetylates RPS20 to inhibit host translation and induce cell cycle arrest - Jiajia Gao; Wenwen Xu; Ziyi Zhou; Lixin Lu; Zhenhuang Ge; Weiqiang Wang; Yongjun Lu; Honghua Ge (Proceedings of the National Academy of Sciences, 2026)
Legionella pneumophila , the causative agent of Legionnaires’ disease, utilizes a type IV secretion system (T4SS) to translocate effectors into host cells, modulating diverse cellular processes to create a replication-permissive niche. Here, we characterize Ceg10, a T4SS-translocated effector, as a nucleus-targeting acetyltransferase that interferes with host ribosome biogenesis and cell cycle progression. Structural analysis reveals that Ceg10 harbors a conserved Cys-His-Asp (CHD) catalytic triad required for its acetyltransferase activity. Upon nuclear import mediated by the host transport adaptor HEATR3, Ceg10 selectively acetylates the ribosomal protein RPS20 at Thr64, Thr65, and Arg66, which have not been annotated as posttranslational modification sites. This acetylation impairs RPS20’s interaction with RPS29 and 18S rRNA, two components critical for 40S ribosomal subunit assembly, leading to translation inhibition and G1/S cell cycle arrest. These host perturbations are essential for efficient early-stage intracellular replication of L. pneumophila . Our findings identify a distinct mechanism by which a bacterial effector co-opts nuclear import machinery and directly modifies ribosomal proteins to subvert host biosynthesis and cell cycle control, highlighting ribosomal protein acetylation as a hitherto unrecognized role in host–pathogen interactions.